2018
DOI: 10.7554/elife.34944
|View full text |Cite
|
Sign up to set email alerts
|

A label-free approach to detect ligand binding to cell surface proteins in real time

Abstract: Electrophysiological recordings allow for monitoring the operation of proteins with high temporal resolution down to the single molecule level. This technique has been exploited to track either ion flow arising from channel opening or the synchronized movement of charged residues and/or ions within the membrane electric field. Here, we describe a novel type of current by using the serotonin transporter (SERT) as a model. We examined transient currents elicited on rapid application of specific SERT inhibitors. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 51 publications
(69 reference statements)
2
27
1
Order By: Relevance
“…The fit revealed that the residual, which had originated from cocaine binding to SERT is comprised of a battery (red trace) and a capacitive component (blue trace) ( Figure 6B-upper panel). This was unexpected and disproved our original claim that the cocaine-induced change in CM was fully attributable to changes in surface potential (8). However, in partial exoneration of this claim, we found that the battery residual accounted in average for a slightly larger part of the change.…”
Section: Analysis Of the Current Responses Recorded From Mammalian Cecontrasting
confidence: 50%
See 4 more Smart Citations
“…The fit revealed that the residual, which had originated from cocaine binding to SERT is comprised of a battery (red trace) and a capacitive component (blue trace) ( Figure 6B-upper panel). This was unexpected and disproved our original claim that the cocaine-induced change in CM was fully attributable to changes in surface potential (8). However, in partial exoneration of this claim, we found that the battery residual accounted in average for a slightly larger part of the change.…”
Section: Analysis Of the Current Responses Recorded From Mammalian Cecontrasting
confidence: 50%
“…Ligand induced capacitance changes are apparent changes. We previously showed that it is possible to monitor ligand binding to membrane proteins in real time by utilizing measurements of the cell membrane capacitance (CM) (8). We investigated the ligand-induced capacitance change in HEK293 cells stably expressing hSERT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations